Islamic Education Values in Short Story Robohnya Surau Kami - Putra, Yoga Mestika; Wardoyo, Cipto; Salahuddin, Amar; Wisman, Wisman (Fakultas Ilmu Budaya, Universitas Jambi, 2024)
This study aims to determine the values of Islamic education in the short story Robohnya Surau Kami by A.A. Navis. This research with a qualitative approach with the concept of content analysis research. Based on the problem formulation, this research focuses on what are the values of Islamic education contained in the short story Robohnya Surau Kami by A.A. Navis. In collecting data, the hermeneutic analysis was used to research and examine short stories, to obtain data to determine the values of Islamic education in the short story. The collected data are grouped and then described. The data that has been collected will be identified, analyzed, and described, which the author then interprets according to the research objectives. The results of this can be used as initial data for future researchers in examining different issues related to this context. Abstrak Penelitian ini bertujuan untuk mengetahui nilai-nilai pendidikan Islam dalam cerpen Robohnya Surau Kami karya A.A. Navis. Penelitian ini dengan pendekatan kualitatif dengan konsep penelitian analisis isi. Berdasarkan rumusan masalah, penelitian ini berfokus pada apa saja nilai-nilai pendidikan Islam yang terkandung dalam cerpen Robohnya Surau Kami karya A.A. Navis. Dalam pengumpulan data, analisis hermeneutika digunakan untuk meneliti dan mengkaji cerpen, guna memperoleh data untuk mengetahui nilai-nilai pendidikan Islam dalam cerpen. Data yang terkumpul dikelompokkan kemudian dideskripsikan. Data yang telah terkumpul akan diidentifikasi, dianalisis dan dideskripsikan, yang kemudian penulis tafsirkan sesuai dengan tujuan penelitian. Hasil penelitian ini dapat digunakan sebagai data awal bagi peneliti selanjutnya dalam mengkaji berbagai permasalahan terkait konteks ini.